2022
DOI: 10.1177/08862605221127215
|View full text |Cite
|
Sign up to set email alerts
|

A Vignettes-Based Exploration of Attitudes of Parents Toward Reporting of Child Sexual Abuse in Ghana

Abstract: Reporting child sexual abuse (CSA) to law enforcement institutions is the ideal child protection imperative. The role of parents in this process is unquestionably profound. Yet, there is limited evidence on parental perspectives on reporting CSA to law enforcement agencies in developing country contexts. We apply vignettes to describe the views of parents about reporting CSA perpetrated by “family members, schoolteachers, and strangers.” Data was collected from 89 parents from four culturally diverse regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…For example, in the research on CSA in Israeli kibbutz communities, one of the main justifications found for silencing victims was to protect the community's reputation and particularly the familial characteristic of the kibbutz, including mutual dependence and trust between the members (Michel and Tener 2023). A similar finding was revealed in the context of reporting CSA in Ghana, where protecting family reputation and maintaining family ties were primary causes for not reporting (Amo-Adjei et al 2023). The issue of family reputation, shame, and stigmatization has been found to be particularly significant in the context of CSA within the Orthodox Jewish community, as reporting CSA may be viewed as disturbing the familial peace and a strike against the family's good name within the community (Katzenstein and Fontes 2017).…”
Section: Familial Justificationmentioning
confidence: 70%
“…For example, in the research on CSA in Israeli kibbutz communities, one of the main justifications found for silencing victims was to protect the community's reputation and particularly the familial characteristic of the kibbutz, including mutual dependence and trust between the members (Michel and Tener 2023). A similar finding was revealed in the context of reporting CSA in Ghana, where protecting family reputation and maintaining family ties were primary causes for not reporting (Amo-Adjei et al 2023). The issue of family reputation, shame, and stigmatization has been found to be particularly significant in the context of CSA within the Orthodox Jewish community, as reporting CSA may be viewed as disturbing the familial peace and a strike against the family's good name within the community (Katzenstein and Fontes 2017).…”
Section: Familial Justificationmentioning
confidence: 70%